2016
DOI: 10.2134/jeq2016.03.0106
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Pharmaceuticals, Heavy Metals, and Herbicides to Biochar in the Presence of Biosolids

Abstract: Agricultural practices are increasingly incorporating recycled waste materials, such as biosolids, to provide plant nutrients and enhance soil functions. Although biosolids provide benefits to soil, municipal wastewater treatment plants receive pharmaceuticals and heavy metals that can accumulate in biosolids, and land application of biosolids can transfer these contaminants to the soil. Environmental exposure of these contaminants may adversely affect wildlife, disrupt microbial communities, detrimentally aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Fine particle emission is an emerging health concern because of the potential of biochar‐bound contaminants. The biochar‐mediated immobilization of heavy metal ions, pesticides, pharmaceuticals, and microbes from the soil is often an intended outcome of biochar application (Bair et al, 2016). Contaminants such as polycyclic aromatic hydrocarbons, heavy metals, dioxins, furans, and polychlorinated biphenyls can be formed or adsorbed in biochar even during biochar production, depending on the feedstock and production temperature (Gelardi et al, 2019; Hale et al, 2012; Yargicoglu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fine particle emission is an emerging health concern because of the potential of biochar‐bound contaminants. The biochar‐mediated immobilization of heavy metal ions, pesticides, pharmaceuticals, and microbes from the soil is often an intended outcome of biochar application (Bair et al, 2016). Contaminants such as polycyclic aromatic hydrocarbons, heavy metals, dioxins, furans, and polychlorinated biphenyls can be formed or adsorbed in biochar even during biochar production, depending on the feedstock and production temperature (Gelardi et al, 2019; Hale et al, 2012; Yargicoglu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, adsorption offers several advantages like flexible design and operation, high removal efficiency, cost-effectiveness and easy regeneration of the adsorbents [ 3 , 7 ]. Thus, several materials have been used for metals adsorption, such as zeolites [ 10 , 11 ], activated carbons [ 12 , 13 ], biochars [ 14 , 15 ], biomaterials [ 16 ], polymers [ 17 ], metal oxides [ 18 , 19 ], nanomaterials [ 20 , 21 , 22 ], and others. So far, nanomaterials have come to the forefront mainly due to their high specific surface area, which is known as one of the main factors determining adsorption magnitude [ 7 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While results showed that BCs were effective in stabilizing pesticide contaminated soils, predicting sorption capacity was made increasingly complicated by cross-effects between BCs and soil. Comparing two BC materials, Bair et al (2016) showed that sorption capacity varied between the two BCs and this difference was magnified by the concomitant addition of biosolids. They also note that for some compounds, namely agrochemicals, sequestration by BCs can limit their efficacy.…”
Section: Activated Carbon and Biocharmentioning
confidence: 99%